2017
DOI: 10.1111/ajt.14029
|View full text |Cite
|
Sign up to set email alerts
|

Treg-Centric View of Immunosuppressive Drugs in Transplantation: A Balancing Act

Abstract: Regulatory CD4+ Foxp3+ T cells (Tregs) are critical in controlling immunity and tolerance. Thus, preserving Treg numbers and function in transplanted patients is essential for the successful minimization of maintenance immunosuppression. Multiple cellular signals control the development, differentiation, and function of Tregs. Many of these signals are shared with conventional Foxp3 T cells (Tconv) and are targeted by immunosuppressive drugs, negatively affecting both Tregs and Tconv. Because intracellular sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 101 publications
(119 reference statements)
0
25
0
Order By: Relevance
“…CNIs produce effective immunosuppression early after transplantation, but have adverse long-term effects for both the patient and the renal allograft (6). CNIs impede the emergence of tolerogenic immune responses, propagating the dependence on maintenance drugs for immunosuppression (7,8). Unlike currently used experimental stem cell regimens, Treg therapies do not require drastic conditioning regimens and do not pose a risk of GVHD (4,9); however, the promising results obtained with Treg infusions in experimental transplantation and autoimmunity models have yet to be fully tested in humans.…”
Section: The Quest For Transplantation Tolerancementioning
confidence: 99%
“…CNIs produce effective immunosuppression early after transplantation, but have adverse long-term effects for both the patient and the renal allograft (6). CNIs impede the emergence of tolerogenic immune responses, propagating the dependence on maintenance drugs for immunosuppression (7,8). Unlike currently used experimental stem cell regimens, Treg therapies do not require drastic conditioning regimens and do not pose a risk of GVHD (4,9); however, the promising results obtained with Treg infusions in experimental transplantation and autoimmunity models have yet to be fully tested in humans.…”
Section: The Quest For Transplantation Tolerancementioning
confidence: 99%
“…Although Tregs are important regulators for alloimmune responses (Adams et al, 2016) in organ and cell transplantation (Camirand and Riella, 2017), the effects of costimulation blockade on Tregs is still unclear. It was assumed that co-stimulation blockade inhibits Treg survival and function (Adams et al, 2016), and an in-vitro study showed that CTLA4-Ig inhibited Treg proliferation (Levitsky et al, 2013).…”
Section: Costimulation Blockade-protected Allogeneic Grps Myelinate Amentioning
confidence: 99%
“…An alternative explanation why there is only an association with l‐BPACR liver transplant recipients and not with e‐BPACR liver transplant recipients may be because of the immunosuppressive treatment. It has been reported that calcineurin inhibitors significantly reduce Treg numbers and Treg development in transplanted patients . Often the dose of calcineurin inhibitors is minimized at a later post‐transplant time point in order to reduce side effects.…”
Section: Demographic and Clinical Characteristics Of Liver Transplantmentioning
confidence: 99%
“…It has been reported that calcineurin inhibitors significantly reduce Treg numbers and Treg development in transplanted patients. 24,25 Often the dose of calcineurin inhibitors is minimized at a later post-transplant time point in order to reduce side effects. This may be the reason why the SNP rs3761548 shows only an association in the late post-transplant phase.…”
mentioning
confidence: 99%